Installation of caisson in non-uniform clay interbedded with a sand layer. (December 2021) - Zhou, Shujin; Zhou, Mi; Zhang, Xihong; Tian, Yinghui
Abstract: Accurately predict the resistance of caisson penetrating in stratified soil deposits is an engineering challenge for application of such foundation system. This paper performs large deformation finite element analysis to investigate the penetration behavior of caisson foundations in non-uniform clay interbedded with a sand layer. The numerical model is validated by comparing with previously testing data, in which good agreement is obtained. Parametric study is then conducted to examine potential influencing factors, including the penetration depth, the top clay layer thickness, clay properties, and the thickness of the second sand layer. It is found that the soil failure mechanism and corresponding penetration resistance of caisson foundations in clay-sand-clay are significantly different from that in pure clay or sand soil deposits, especially for the part in the middle sand layer, where the peak resistance could be overestimated by 10–40% using the current design codes without considering the influence of the weak underlying layer. In this study, based on intensive numerical modeling results, approximating expressions are proposed to describe the unique trends of the resistance profile for caisson penetration in non-uniform clay interbedded with a sand layer soil deposit, which can provide design guide for engineering application.